Pola Pikir, Karakter, dan Motivasi sebagai Penentu Keberhasilan Wirausaha - Ibrahim, Muhammad Maulana; Utami, Rizki Amalia; Rahayu, Wening Patmi; Winarno, Agung (FEB Universitas Maritim Semarang, 2025)
Entrepreneurship plays a significant role in global economic growth. However, not all entrepreneurs achieve success. This study aims to deeply examine the mindset and character that serve as the fundamental basis for entrepreneurial success, as well as the influencing factors and strategies for fostering these qualities based on a literature review. Through a literature review method, it was found that successful entrepreneurs possess a growth mindset, are solution-oriented, and adaptive, supported by specific thinking methods like BETSCA (Bricolage, Effectuation, Think Structurally, Cognitive Adaptability). Furthermore, key characters such as commitment, creativity, resilience, risk-taking propensity, and networking ability are crucial elements. The study also identified various driving factors and types of motivation (intrinsic-extrinsic) in entrepreneurship. Another important finding is that the entrepreneurial spirit and character can be learned and developed through personal commitment, a supportive environment, education, and continuous learning processes. The conclusion of this study asserts that the combination of the right mindset and strong character, along with the ability to continuously develop both, is essential for increasing the chances of success in the world of entrepreneurship.